Identification of a Novel Mutation in TNFAIP3 in a Family With Poly-Autoimmunity - Rossi, Marianna Nicoletta; Federici, Silvia; Uva, Andrea; Passarelli, Chiara; Celani, Camilla; Caiello, Ivan; Matteo, Valentina; Petrocchi, Stefano; Mortari, Eva Piano; De Benedetti, Fabrizio; Prencipe, Giusi; Insalaco, Antonella (Frontiers in Immunology, 2022)
Haploinsufficiency of A20 (HA20) is an inflammatory disease caused by mutations in the TNFAIP3 gene classically presenting with Behcet’s-like disease. A20 acts as an inhibitor of inflammation through its effect on NF-kB pathway. Here we describe four consanguineous patients (three sisters and their mother) with a predominantly autoimmune phenotype, including thyroiditis, type I diabetes, hemolytic anemia and chronic polyarthritis. All patients had recurrent oral ulcers, with only 1 patient presenting also recurrent fever episodes, as a classical autoinflammatory feature. Next generation sequencing identified a novel heterozygous frameshift mutation (p.His577Alafs*95) that causes a premature stop codon in the zinc finger domain of A20, leading to a putative haploinsufficiency of the protein. Functional analyses confirmed the pathogenicity of the mutation. The variant was associated with decreased levels of A20 in blood cells. Accordingly, ex-vivo lipopolysaccharide (LPS)-stimulated patients’ peripheral blood mononuclear cells (PBMCs) showed higher levels of p65 NF-kB phosphorylation, as well as increased production of the proinflammatory cytokines IL-1β, IL-6 and TNF-α. Moreover, in agreement with recent observations, demonstrating a role for A20 in inhibiting STAT1 and IFNγ pathways, markedly higher circulating levels of the two IFNγ-inducible chemokines CXCL9 and CXCL10 were detected in all patients. Supporting the findings of a hyperactivation of IFNγ signaling pathway in HA20 patients, patients’ monocytes showed higher levels of STAT1 without stimulation, as well as higher phosphorylated (active) STAT1 levels following IFNγ stimulation. In conclusion, our study show that in the clinical spectrum of HA20 autoimmune features may predominate over autoinflammatory features and demonstrate, from a molecular point of view, the involvement of A20 in modulating not only the NF-kB, but also the IFNγ pathway.